Two new polymorphic forms of combretastatin A‐4, an antitumour agent. Issue 10 (22nd September 2020) - Grześkiewicz, Anita M.; Stefański, Tomasz; Dutkiewicz, Zbigniew; Buśko, Daria; Kubicki, Maciej
Abstract : Two new polymorphic forms of combretastatin A‐4, an inhibitor of tubulin polymerization at the colchicine binding site, were identified. The results confirm the role of weak interactions in the determination of crystal architecture and additionally hint at an explanation for the results of crystallization attempts: the new monoclinic form has significantly lower energy than the form reported earlier. Abstract : Two new polymorphic forms of combretastatin A‐4 {systematic name: 2‐methoxy‐5‐[( E )‐2‐(3, 4, 5‐trimethoxyphenyl)ethenyl]phenol, C18 H20 O5, CA‐4}, an inhibitor of tubulin polymerization at the colchicine binding site, were identified. A number of crystallization attempts led to the orthorhombic form, with two molecules in the asymmetric part of the unit cell; obtaining a different form required the experiment to be moved to another laboratory. None of the attempts resulted in the monoclinic form described earlier. The three different forms contain molecules of significantly different geometries, which can be related to conformational freedom, postulated as the result of biological studies. In addition, the packing modes in all three forms are basically different. The structural differences at both the molecular and the supramolecular level have also been studied via calculations of energies and a topological analysis of the electron density. The results confirm the role of weak interactions in the determination of crystal architecture and additionally hint at an explanation for the results of crystallization attempts: the new monoclinic form has significantly lower energy than the form reported earlier.